Antifungal Activity Test of the Ethanol Extract of Kaembu-embu (Blumea balsamifera) Leaves Against the Fungus C. albicans Growth - Nasriadi Dali Wela; Arniah Dali Wela; Seniwati Dali; Armadi Chairunnas; Hilda Ayu Melvi Amalia; Sri Ayu Andini Puspitasari (ALCHEMY:Journal of Chemistry, 2022)
AbstractResearch on the antifungal activity test of ethanol extract of Kaembu-embu (Blumea balsamifera) leaves against the fungus C. albicans growth was carried out. The aim of this study was to examine the antifungal activity of ethanol extracts of Kaembu-embu (Blumea balsamifera) leaves on the growth of the fungus C. albicans. The ethanol extract of Kaembu-embu (Blumea balsamifera) leaves was obtained through maceration method. The ethanol extract of Kaembu-embu (Blumea balsamifera) leaves was tested for antifungal activity by liquid and solid dilution methods in determining minimum inhibitory concentration (MIC) and minimum kill concentration (MKC). The results of the antifungal activity of the ethanol extract of Kaembu-embu (Blumea balsamifera) leaves on the growth of the fungus C. albicans by the liquid dilution method showed the MIC value of 25 ppm and MKC value of 500 ppm. While the results of the antifungal activity of the ethanol extract of Kaembu-embu (Blumea balsamifera) leaves on the growth of the fungus C. albicans by solid dilution method showed the MIC value of 5 ppm with inhibitory ability of 50.13% of media control and a MKC value of 250 ppm.